ANALISIS DRAMA KADERA KARYA DIDIT MARCHEL DENGAN PENDEKATAN SEMIOTIKA PIERCE - Nurrahma, Nurrahma; Musawir, Muhammad; Hasbi, Nur (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2024)
This study aims to determine the symbols and meanings of the symbols contained in the drama Kadera by Didit Marchel. The approach used in this study is Charles Sanders Pierce's semiotic approach. This type of research is descriptive qualitative. The data analysis technique is by: (1) reading and understanding the contents of the drama text in detail, (2) identifying the symbols contained in the text, (3) summarizing the symbols and meanings of the text contained in the drama. The results of the study indicate that the drama Kadera by Didit Marchel has a text structure: characters, events, conflicts, plots, and backgrounds. The symbols found in the drama Kadera by Didit Marchel can be interpreted after being explained using a semiotic approach. The symbols found are in the form of words and sentence structures in the form of figurative language and terms, such as kaki tangan which means subordinates who become assistants to a leader and wetlands as a symbol of a strategic position in a position.